Upstream Thrombus Growth Impairs Downstream Thrombogenesis in Non-Anticoagulated Blood: Effect of Procoagulant Artery Subendothelium and Non-Procoagulant Collagen - Sakariassen, Kjell S; Weiss, Harvey J; Baumgartner, Hans R (Thrombosis and Haemostasis, 1991)
In the present experiments we have investigated the influence of wall shear rate and axial position on platelet and fibrin deposition which results when flowing human non-anticoagulated blood is exposed to either non-procoagulant fibrillar collagen (human type III) or procoagulant subendothelium (rabbit aorta). Platelet adhesion, thrombus volume and fibrin deposition were morphometrically evaluated at axial positions of 1 and 13 mm following perfusions for 5 min at shear rates of 100, 650 and 2,600 s-1.An axially-dependent decrease of platelet adhesion (34-57%, p <0.01-0.05) and thrombus volume (57-80%, p <0.05) was observed on collagen at all shear rates. On subendothelium, an axially-dependent decrease was observed for platelet adhesion only at 100 s-1 (29% ; p <0.01) and for thrombus volume at shear rates of 650 s-1 and above (49-58%, p <0.01). Deposition of fibrin on subendothelium was axially decreased (16-42%, p <0.05) at all shear rates, while no significant axial differences were seen on collagen. However, substantially more fibrin was deposited on the subendothelium (p <0.05), and the upstream platelet adhesion and thrombus volume were lower than on collagen (p <0.05) at 100 s-1 and 650 s-1. The axially-dependent phenomena on the two surfaces are consistent with the concept of rapid-growing upstream thrombi which deplete the blood layer streaming adjacent to the surface of platelets, leading to decreased platelet deposition farther downstream. The observations suggest that deposition of fibrin is enhanced by subendothelial tissue factor, and that upstream depletion of clotting factors may lower the downstream deposition of fibrin, analogous to the depletion of platelets.